Teachers' Understanding of Authentic Assessment Procedures for Islamic Studies Education Subjects at SMP Al-Asy'ari Sumatera Utara - Zahrotul Husna; Adam Baihaqi; Rizky Amanda Nasution; Iskandarsyah Iskandarsyah; Neliwati Neliwati (UMSU, 2023)
The research discusses the teachers' understanding of authentic assessment in Islamic Religious Education subjects at Al-Asy'ari Junior High School. The method used in the research is a qualitative approach with the research method being the type of field research (field research). The theme of the study was the understanding of Islamic Religious Education teachers regarding authentic assessment. The results of the study showed that the teachers in the planning stage were in the good enough category with a percentage of 57.33%. The implementation stage with the category is quite good with a percentage of 43.33%. The reporting stage is quite good with a percentage of 48%. Based on this percentage, there are still related obstacles, from these obstacles there should be a coordinator and also training for teachers on how to implement the 2013 curriculum assessment and learning.